Psychiatric morbidity and readiness for change : a study of methamphetamine dependent subjects in Cape Town - Akindipe, Taiwo (Department of Psychiatry and Mental Health, 2014)
Methamphetamine users may suffer from a range of co-morbid psychiatric disorders. Predictors of treatment outcome in substance dependence may include both such co-morbidity and readiness for change. The nature of the relationship between psychiatric co-morbidity and readiness for change has not been systematically studied. Therefore, this study aimed to assess the prevalence and patterns of psychiatric disorders in individuals dependent on methamphetamine; determine whether there is a relationship between such co-morbidity and readiness for change; and identify factors associated with readiness for change in this group.